Myoinositol in Autoimmune Thyroiditis - Paparo, Sabrina Rosaria; Ferrari, Silvia Martina; Patrizio, Armando; Elia, Giusy; Ragusa, Francesca; Botrini, Chiara; Balestri, Eugenia; Guarneri, Fabrizio; Benvenga, Salvatore; Antonelli, Alessandro; Fallahi, Poupak (Frontiers in Endocrinology, 2022)
Myoinositol (Myo) is an isoform of inositol, a cyclic polyol with 6 hydroxyl groups. Myo mainly derives from dietary intake while its endogenous production is generated from glucose by enzymatic reactions. Moreover, Myo is also synthesized de novo by catabolism of phosphatidylinositol (PI), phosphoinositides (PIP), and inositol phosphates (IP). Myo has a determinant role in thyroid function and autoimmune diseases: it regulates iodine organification and thyroid hormone biosynthesis by the formation of hydrogen peroxide (H2O2) in thyrocytes. Depletion of Myo, that is involved in the thyroid stimulating hormone (TSH) signaling pathway, may cause the development of thyroid diseases, such as hypothyroidism. TSH levels significantly result decreased in patients with subclinical hypothyroidism with or without autoimmune thyroiditis, after treatment with Myo plus Selenium (Myo+Se). In addition to TSH, even antithyroid autoantibodies are reduced. This review summarizes the role of Myo, in the thyroidal physiology and its role in the management of some thyroid diseases.